Hepatoprotective activity of methanolic leaves extract of Rostellularia procumbens by using carbon tetrachloride intoxicated rats - Mamatha, M.; Manasa, V.; Vijusha, M.; Suthakaran, R. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Rostelluria procumbens is a medicinal plant used traditionally in the treatment of asthma, cough and constipation and as an antioxidant etc. it is rich in phytochemical compounds, which are responsible for its biological properties. The present study focused on evaluation of hepatoprotective activity of methanolic extract of R. procumbens leaf in carbon tetrachloride (CCl4) induced hepatotoxocity in rats. Methods: In this study, 30 wistar rats were used and grouped into 6 each group contain 6 rats. In this study, CCl4 is used as hepatotoxin. Four groups were treated with CCl4 and taken as disease control, standard, and two test groups. One group was taken as control treated with saline. Blood samples were collected and estimated serum glutamate oxaloacetate transaminase, serum glutamate pyruvate transaminase, alkaline phosphatase and total bilirubin, which are key markers of liver function. The rats were sacrificed and livers were isolated and histopatological studies carried out. Results: On oral administration of methanolic leaves extract of R. procumbens to ethanol intoxicated, rats resulted in significant restoration of enzyme levels and also silymarin at a dose of 25 mg/kg. The reversal of increased serum enzymes in ethanol-induced liver damage by the extract may be due to the prevention of leakage of intracellular enzymes by its membrane stabilizing activity. Conclusion: The results confirm that R. procumbens have hepatoprotective activity againstCCl4 induced hepatotoxicity and significant hepatoprotection seen at 500 mg/kg dose.